Board Diving Regulations in Public Swimming Pools and Risk of Injury. Issue 6 (17th November 2015) - Williams, David; Odin, Louise
Abstract : Public session access to diving boards is one of the stepping stones for those wishing to develop their skills in the sport of diving. The extent to which certain dive forms are considered risky (forward/backward/rotations) and therefore not permitted is a matter for local pool managers. In Study 1, 20 public pools with diving facilities responded to a U.K. survey concerning their diving regulation policy and related injury incidence in the previous year. More restrictive regulation of dive forms was not associated with a decrease in injuries ( rs [42] = –0.20, p = 0.93). In Study 2, diving risk perception and attitudes towards regulation were compared between experienced club divers ( N = 22) and nondivers ( N = 22). Risk was perceived to be lower for those with experience, and these people favored less regulation. The findings are interpreted in terms of a risk thermostat model, where for complex physical performance activities such as diving, individuals may exercise caution in proportion to their ability and previous experience of success and failure related to the activity. Though intuitively appealing, restrictive regulation of public pool diving may be ineffective in practice because risk is not simplistically associated with dive forms, and divers are able to respond flexibly to risk by exercising caution where appropriate.